The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11104-020-04605-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium decreases aluminum accumulation and plays a role in protecting maize from aluminum-induced oxidative stress

Abstract: BackgroundAcidic soils with a pH water below 5.5 occupy up to 40% of world's arable land. Aluminum (Al) toxicity and magnesium (Mg) deficiency often coexist in acidic soils, limiting crop production. In this study, we investigated a role of Mg in alleviation of Al stress in maize (Zea mays) by characterizing the growth responses, Al accumulation and the antioxidant properties of plants cultured hydroponically. MethodsPhysiological and molecular analyses were used to investigate the mechanisms of Mg governing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Similarly, Kong et al showed that the addition of Mg to the Al treatment solution alleviated Al-induced inhibition of root growth, suppressed Al uptake, and reduced hydrogen peroxide (H 2 O 2 ) concentration in maize [99]. Furthermore, K + efflux was related to Al tolerance by accompanying OA secretion [99]. Recently, Li et al showed that ectopic expression of either HtNHX1 or HtNHX2, from Jerusalem artichoke (Helianthus tuberosus), could enhance rice tolerance to Al stress and soil acidity by altering K + and H + fluxes and the CW structure [41].…”
Section: Internal Tolerance Mechanismsmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, Kong et al showed that the addition of Mg to the Al treatment solution alleviated Al-induced inhibition of root growth, suppressed Al uptake, and reduced hydrogen peroxide (H 2 O 2 ) concentration in maize [99]. Furthermore, K + efflux was related to Al tolerance by accompanying OA secretion [99]. Recently, Li et al showed that ectopic expression of either HtNHX1 or HtNHX2, from Jerusalem artichoke (Helianthus tuberosus), could enhance rice tolerance to Al stress and soil acidity by altering K + and H + fluxes and the CW structure [41].…”
Section: Internal Tolerance Mechanismsmentioning
confidence: 98%
“…Further experiment showed that raised pH alleviates Al-induced a decrease in total soluble protein level and an increase in electrolyte leakage in citrus leaves and roots by conferring the ability to maintain a balance between production and detoxification of ROS and methylglyoxal [92]. Moreover, Liu et al's study on wild barley showed that low pH and higher Al tolerance in XZ16 were associated with a higher ability of H + uptake and rhizospheric alkalization [99]. Magnesium promotes the elevated root surface pH regulation in Populus, resulting in root surface alkalization in the transition zone, which alleviates the toxicity of high concentration Al [100].…”
Section: External Exclusion Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Mg is fundamental for a series of enzymatic activities and the synthesis of some proteins (Marschner, 2011;Shaul, 2002). Recent studies have also revealed a role of Mg in relieving stress caused by adverse growth conditions, such as aluminum, Mn and Pb toxicity (Bose et al, 2011;Kong et al, 2020;Gransee & Führs, 2013;Shen et al, 2016), photooxidative damage (Cakmak & Kirkby, 2008;Hauer-Já kli & Trä nkner, 2019), and heat stress (Mengutay et al, 2013;Siddiqui et al, 2018).…”
Section: Thementioning
confidence: 99%
“…Similarly, appropriate Mg nutrition mitigates the detrimental effects of Al toxicity in plants. In this Special Issue, Kong et al (2020) show that an adequate Mg supply reduces Al uptake and improves the growth of maize plants exposed to high Al concentrations in the rhizosphere. Increasing Mg supply also increased the antioxidative capacity of maize plants and promoted the expression of genes encoding superoxide dismutase, catalase and peroxidase when plants were exposed to Al stress.…”
mentioning
confidence: 93%